(untitled) (Research, Society and Development, 2021)
The objective was to demonstrate the use of medicinal plants by individuals from a community in Acre. This is a descriptive and exploratory study, with a qualitative approach, based on interviews conducted with 21 individuals, of both sexes, living in the vicinity of a peripheral neighborhood in the city of Rio Branco - Acre, in whose locality they are located, a community garden with the cultivation of medicinal plants. The population participating in the study was mostly female, aged between 54 and 80 years old and used medicinal plants frequently, in addition to recommending them to family and friends. Most learned about the use plants from their mothers and grandmothers. About 32 species were cited as being used for the most varied treatments, most of which used herbs in the form of tea. They expressed that the practices of the use of herbal medicines can help improve the health status of those who use them and that they believed in their healing power, as they had their own experiences from their use. The population studied uses medicinal plants, based only on their traditional popular knowledge and on the indication of others, which highlights the need to carry out research for better knowledge and dissemination of information on therapeutic and toxic properties in order to avoid future complications.